An Overview of ARTMIP's Tier 2 Reanalysis Intercomparison: Uncertainty in the Detection of Atmospheric Rivers and Their Associated Precipitation. Issue 8 (18th April 2022) - Collow, A. B. Marquardt; Shields, C. A.; Guan, B.; Kim, S.; Lora, J. M.; McClenny, E. E.; Nardi, K.; Payne, A.; Reid, K.; Shearer, E. J.; Tomé, R.; Wille, J. D.; et al.
Abstract: Atmospheric rivers, or long but narrow regions of enhanced water vapor transport, are an important component of the hydrologic cycle as they are responsible for much of the poleward transport of water vapor and result in precipitation, sometimes extreme in intensity. Despite their importance, much uncertainty remains in the detection of atmospheric rivers in large datasets such as reanalyses and century scale climate simulations. To understand this uncertainty, the Atmospheric River Tracking Method Intercomparison Project (ARTMIP) developed tiered experiments, including the Tier 2 Reanalysis Intercomparison that is presented here. Eleven detection algorithms submitted hourly tags‐‐binary fields indicating the presence or absence of atmospheric rivers‐‐of detected atmospheric rivers in the Modern Era Retrospective Analysis for Research and Applications, version 2 (MERRA‐2) and European Centre for Medium‐Range Weather Forecasts' Reanalysis Version 5 (ERA5) as well as six‐hourly tags in the Japanese 55‐year Reanalysis (JRA‐55). Due to a higher climatological mean for integrated water vapor transport in MERRA‐2, atmospheric rivers were detected more frequently relative to the other two reanalyses, particularly in algorithms that use a fixed threshold for water vapor transport. The finer horizontal resolution of ERA5 resulted in narrower atmospheric rivers and an ability to detect atmospheric rivers along resolved coastlines. The fraction of hemispheric area covered by ARs varies throughout the year in all three reanalyses, with different atmospheric river detection tools having different seasonal cycles. Key Points: Enhanced integrated water vapor transport in MERRA‐2 leads to increased detection of atmospheric rivers in algorithms with fixed thresholds relative to JRA‐55 and ERA5 Algorithms that use relative thresholds have better agreement between reanalyses than those with absolute thresholds Algorithms result in conflicting seasonal cycles of the average hemispheric area covered by atmospheric rivers